Food safety in Latin American informal food establishments - Pariza, Teodora; Cho, Min Jung (Frontiers in Sustainability, 2024)
Informal food establishments are an important source of food due to their increased affordability of products and convenience. They are an essential part of the food system and are thus affected by the same challenges. In Latin America, the safety of food is less analyzed than food security, although it is central to people's health, as well as to their personal sustainability. Since informal food establishments are popular food sources in Latin America, this research aims to examine the presence of foodborne pathogens in food products from such establishments. This research will be conducted as narrative literature review, collecting data from all Spanish-speaking countries in Latin America. The timeline of interest for the published literature starts with the year 2018. The search included pathogens such as bacteria, parasites and viruses. The analysis was based on 32 articles. The widest variety of pathogens was among bacteria. The most frequently identified bacteria belonged to the genus Escherichia. The food products examined ranged from animal products to fruit and vegetables, fish, seafood and already prepared dishes or juices. The informal food establishments where the studies conducted their analyses were markets, backyard selling points, street establishments or convenience food stores. Identifying pathogens in food products commercialized at different informal retail points has impacts for the safety of the food from a personal sustainability viewpoint. Further investigation could trace the exact sources of infection, while public health officials can implement safety programs in cooperation with food vendors.